PENGARUH JENIS PUPUK DAUN DAN JENIS MULSA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAYAM MERAH (Amaranthus tricolor L.) VARIETAS BISI - Nurmas, Andi; Fitriah, Sitti Putri (Jurnal Agroteknos, 2011)
ABSTRACTThe objective of this experiment was to study the effect of foliar fertilizer type and mulch  type  on  the  growth  and  production of  red  spinach  (Amaranthus tricolor L.)  bisi variety. The experiment was conducted from July to September 2010 in the Village District Padaleu Poasia Kendari. The research was based on randomized block design (RBD) in the factorial pattern consisting of two factors, with three replications. The first factor was the type of foliar fertilizer which consisted of 4 levels: without foliar fertilizer (K0), Gandasil-D (K1), Bayfolan (K2), Seprint (K3). The second factor was the type of mulch which consisted of 3 types, namely: no mulch (M0), plastic black silver mulch (M1), and reed leaves (M2). The results showed  that  in  general the  interaction between foliar  fertilizer of  Bayfolan and plastic  mulch  (MPHP)  gave  a  significant  effect  on  the  growth  and  yield  of  red  spinach (Amaranthus tricolor L.) bisi variety. Keywords : Red Spinach, Foliar Fertilization Mulch